“Every Child Is Special…”: Perspectives on the Integration of Children Born of War and Their War-Affected Peers at a Local School in Northern Uganda - Boniface Ojok (Frontiers in Political Science, 2022)
This article examines the circumstances of 16 Children Born of War (CBOW) who participated in a classroom activity designed to understand their experiences of integration at a local school in post war northern Uganda. The children are part of a generation of returnees who were conceived as a result of sexual violence and forced marriages between the commanders of the Lord's Resistance Army (LRA) and young girls abducted from their communities. The research at the Alur Primary School (APS) articulates the children's views, and how this one school managed to integrate CBOW and war-affected children, treating each as special, to advance their learning and their education. Specifically, each of the 181 war-affected children involved in the class activity was given a chance to recall key moments of their time at APS. Their write-ups were analyzed into themes illustrating what happened when CBOW were integrated into the school, and how the school responded to their educational needs. The activity did not isolate CBOW from their non-CBOW peers, hence giving every child the opportunity to freely express their views regardless of their background. This article contributes to our understanding of how schools, as one of the most influential institutions that shape the development of children, can foreground the voices of CBOW as beneficiaries of education and actors in their own right.